2021
DOI: 10.3390/ijms22094993
|View full text |Cite
|
Sign up to set email alerts
|

Relative Importance of Soluble and Microsomal Epoxide Hydrolases for the Hydrolysis of Epoxy-Fatty Acids in Human Tissues

Abstract: Epoxy-fatty acids (EpFAs) are endogenous lipid mediators that have a large breadth of biological activities, including the regulation of blood pressure, inflammation, angiogenesis, and pain perception. For the past 20 years, soluble epoxide hydrolase (sEH) has been recognized as the primary enzyme for degrading EpFAs in vivo. The sEH converts EpFAs to the generally less biologically active 1,2-diols, which are quickly eliminated from the body. Thus, inhibitors of sEH are being developed as potential drug thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…An accumulation of 7,8 epoxydocosapentaenoic acid, and a decrease of the corresponding diol (7,8 dihydroxydocosapentaenoic acid), was observed ( Figure 2—figure supplement 1 ). A recent study shows that mEH plays a significant role in the metabolism of this EpFA ( Morisseau et al, 2021 ). Since oxylipin profiling is an emerging field, whose biological interpretation remains difficult, further experiments will be required to confirm this observation in additional patients and/or different cellular models.…”
Section: Resultsmentioning
confidence: 99%
“…An accumulation of 7,8 epoxydocosapentaenoic acid, and a decrease of the corresponding diol (7,8 dihydroxydocosapentaenoic acid), was observed ( Figure 2—figure supplement 1 ). A recent study shows that mEH plays a significant role in the metabolism of this EpFA ( Morisseau et al, 2021 ). Since oxylipin profiling is an emerging field, whose biological interpretation remains difficult, further experiments will be required to confirm this observation in additional patients and/or different cellular models.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that sEH and mEH enzyme levels were also increased in DCM hearts suggesting rapid-turnover of newly synthesized or liberated EpFAs. sEH is the primary epoxide hydrolase responsible for the metabolism of EpFAs throughout the body ( 39 ). mEH plays a less prominent role, but contributes to hydrolysis of residual EpFAs which escape sEH-dependent metabolism ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…sEH is the primary epoxide hydrolase responsible for the metabolism of EpFAs throughout the body ( 39 ). mEH plays a less prominent role, but contributes to hydrolysis of residual EpFAs which escape sEH-dependent metabolism ( 39 ). Enhanced sEH expression and activity is associated with CVD, likely via the metabolism of cardioprotective and anti-inflammatory EpFAs in the heart ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies determined the specificity of both omega-3 and -6 fatty acid epoxides for the sEH enzyme and also determined that the LA epoxides had the highest affinity, demonstrated by the lowest K m , of all epoxide regioisomers from different PUFA lipids tested with the exception of a few lipids ( cis and trans 9,10-EpO, γ-12,13-EpODE, and 11,12-EET). Furthermore, sEH metabolizes the 12,13-EpOME slightly faster than the 9,10-EpOME; however, the lack of statistical significance in decreasing 9,10-DiHOME after TPPU treatment can be explained by non-sEH hydrolysis by the structurally and catalytic very different epoxide hydrolase enzyme, microsomal epoxide hydrolase, which can hydrolyze the 9,10- but not the 12,13-EpOME and not as efficiently as sEH ( 43 ). This is consistent with the oxylipin profile showing elevated DiHOMEs from burned mice, suggesting higher activity of the sEH enzyme in response to burn and the importance of inhibiting the formation of these metabolites.…”
Section: Discussionmentioning
confidence: 99%